Menuju Etika Ekonomi dalam Perspektif Islam - Muhammad Akhyar Adnan (Universitas Islam Indonesia, 2005)
The article below investigates islamic economics. The study on Islamic economics includes at least two main problems, (1) how the ethics of business from Islam view point, and (2) how the ethics of economcs according to islam perspective. According to the author that the ethics of economics is not only in islam, but also in other religion. But, Islam involves ethics, islamic ethics sources from verified teaching and universal doctrine, besides, it can be an alternative economical recovery solution. For realizing Islamic ethics regarding economics, it needs socializing and implementing by discourse and the Islamic subjects and technological supporting.